Short-Lasting Unilateral Neuralgiform Headache Attacks with Conjunctival Injection and Tearing in a Patient with Varicella-Zoster Virus Encephalomyelitis - Megan E. Gray; Brian Wispelwey; Christopher J. Arnold (Case Reports in Infectious Diseases)
Short-lasting unilateral neuralgiform headache attacks with conjunctival injection and tearing syndrome (SUNCT) is a type of trigeminal autonomic cephalalgia. Its etiology is generally idiopathic, though rarely it has been associated with viral infections. We describe the fourth case reported in the literature of SUNCT in association with viral meningoencephalitis.